2002
DOI: 10.1901/jeab.2002.78-271
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Linked Perceptual Classes

Abstract: Multiple-exemplar training with stimuli in four domains induced two new fill-based (A1' and A2') and satellite-image-based (B1' and B2') perceptual classes. Conditional discriminations were established between the endpoints of the A1' and B1' classes as well as the A2' and B2' classes. The emergence of linked perceptual classes was evaluated by the performances occasioned by nine cross-class probes that contained fill variants as samples and satellite variants as comparisons, along with nine other cross-class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…A number of studies have identified training and testing parameters that broaden the range of variants that come to function as members of generalized equivalence classes. (Belanich & Fields, 2003;Fields et al, 1991Fields et al, , 2002Fields & Reeve, 2001;Galizio, Stewart, & Pilgrim, 2004). Perhaps the generalization problems reported by Cowley et al and Lynch and Cuvo could be overcome by the inclusion of the above-mentioned parameters in replications of their experiments.…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have identified training and testing parameters that broaden the range of variants that come to function as members of generalized equivalence classes. (Belanich & Fields, 2003;Fields et al, 1991Fields et al, , 2002Fields & Reeve, 2001;Galizio, Stewart, & Pilgrim, 2004). Perhaps the generalization problems reported by Cowley et al and Lynch and Cuvo could be overcome by the inclusion of the above-mentioned parameters in replications of their experiments.…”
Section: Discussionmentioning
confidence: 96%
“…The FR-based responses and corresponding ratio values were used in the present experiment because the results of prior experiments had shown that discriminations that used similarly defined responses were acquired with little training and were maintained with very high accuracy under extinction conditions (Belanich & Fields, 2003;Fields et al, 1995). Different keys of the computer keyboard were not used as the responses because they could be construed as comparison stimuli in a trial (Fields, Tittelbach, et al, 2007). Under those circumstances, instead of forming a simple discrimination between a class member and an operant, a subject would be selecting among comparison stimuli and forming a conditional discrimination between two stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…As the value of the anchor stimulus in each class was arbitrarily set to zero, the width of each class was indexed by the value of the boundary stimulus for that class. Previous research had shown that the value of the boundary stimulus in a perceptual class can vary as a function of whether it is used as a sample or as a comparison (Fields et al, 2002a;Fields et al, 2002b;Fields et al, 2005). In Phase 3, the values of the boundary stimuli when used as samples were determined using variant-to-base generalization tests, and the values of the boundary stimuli when used as comparisons were determined using base-to-variant generalization tests.…”
Section: Methodsmentioning
confidence: 99%